Design AI In Digital Marketing (Cross Salling Method) - Siti Sufaidah; Taufiqur Rohman Asyari (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this research is to produce an Online Shop application that can be used to fulfill the market demand and seek new market opportunities. Type of the experiment using the case study method of research and development and data collection techniques used were observation, interviews, and documentation studies. The research instruments include procedures applicable to covers aspects of the website features are required Pasar Temayang Management product (category, product details, pricing, pictures, promotion, discount management, stock management), order management, including search for orders, update order status. Produce the features of Online Shop application it gives a lot of convenience, from the booking to the payment and receipt of the payment process and all reports relating to the sale and fulfillment marketing. Keywords: web-base Online Shop application, research and development, incremental development approach